The truth about twinkie pie - Yet, Kat (New York : SCHOLASTIC, 2015)
The truth about twinkie pie There's something about asking for impossible Things. For one little second, they feel Possible. Take two sisters making it on their own: brainy twelve-year-old GiGi and junior-high-dropout-turned-jairrtylist DiDi. Add a million dollars in prize money from a national cooking contest and a move from the trailer parts of South Carolina to the North Shore of Long Island. Mix in a fancy new school, new friends and enemies, a first crush, and a generous sprinkling of family secrets.
La verdad sobre el pastel twinkie. Hay algo acerca de pedir cosas imposibles. Por un pequeño segundo, se sienten posibles. Toma a dos hermanas que lo hagan solas: el inteligente GiGi, de doce años, y DiDi, que abandona la escuela secundaria y se convierte en joven. Agregue un millón de dólares en premios de un concurso nacional de cocina y una mudanza desde las partes del remolque de Carolina del Sur hasta la costa norte de Long Island. Mezcle una nueva y elegante escuela, nuevos amigos y enemigos, un primer enamoramiento y una generosa cantidad de secretos familiares.
Keywords: NORTH AMERICAN LITERATURE -- NOVEL; LITERATURA NORTEAMERICANA -- NOVELA